Luminescent lanthanide–organic polyrotaxane framework as a turn-off sensor for nitrobenzene and Fe3+. Issue 23 (17th February 2016) - Cao, Xiao-Man; Wei, Na; Liu, Lin; Li, Li; Han, Zheng-Bo
Abstract : Three isomorphous lanthanide–organic polyrotaxane frameworks [Ln(mtpc)1.5 (DMA)(H2 O)]·2H2 O [Ln = Tb (1 ); Dy (2 ); Er (3 )] were assembled and characterized.1 acts as a fluorescent probe for nitrobenzene and iron(iii ) ions, and the detection limit of nitrobenzene is 15–150 ppm. Abstract : Three isomorphous lanthanide–organic polyrotaxane frameworks [Ln(mtpc)1.5 (DMA)(H2 O)]·2H2 O [Ln = Tb (1 ); Dy (2 ); Er (3 )] were assembled and characterized. In1, the mtpc ligand transfer absorbed energy to Tb 3+ center to emit characteristic fluorescence.1 can act as a fluorescent probe for selectively detecting nitrobenzene and iron(iii ) ions through luminescence quenching. Importantly, the detection limit of nitrobenzene is on the 15–150 ppm scale.